Preferensi Petani Pesisir Pantai Selatan Kabupaten Purworejo terhadap Varietas Unggul Baru Padi (Oryza sativa) - Umi Barokah; Teguh Wibowo; Mastsani Durrotul Jannah; Lulu Lazimatul Khoiriyah; Trias Sitaresmi (JURNAL PANGAN, 2026)
Background: Purworejo Regency is one of Indonesia's rice-producing regions. Identifying new, superior varieties suitable for various soil types, such as saline soils, is expected to increase rice production in the region. Objectives: The purpose of this study is to provide recommendations for new superior rice varieties based on the highest productivity in saline land in Purworejo Regency, and to create a sustainable agricultural management model. Methods: This study uses PVS tests that can be used in other areas with similar characteristics. This study involved 17 respondents to determine the preferences of each new superior rice variety. Respondents were selected through observation and recommendations from Gapoktan based on the number of farmers active in the rice fields. Observations were also made on new superior rice varieties in the vegetative and generative phases. Observations in the generative phase, including crop yields. Parameters for observation of morphological characters include plant height (cm), number of seedlings, root length (cm), flowering age 50%, number of panicles, number of filled grains, number of empty grains, and weight of filled grain.Results and Discussion: The results of the PVS test, based on farmers' preferences for the presented superior rice varieties, were analyzed using descriptive statistics. The results of this assessment will be balanced against the study's average parameters for each variety. Through the PVS test approach and participatory preference data collection, the Inpari 34 Agritan variety emerged as the main choice, with lower farmer acceptance due to weakness in pest resistance and low productivity, despite its superior characteristics based on morphological observations. In contrast, varieties such as IPB 12S and TP-Padi 2 show relatively lower acceptance among farmers due to weaknesses in pest resistance and low productivity Conclusion: The PVS approach is effective for selecting salt-tolerant rice varieties that are well-suited to farmers’ needs and have the potential to support food security.